Mortality Rate of Lymphoma in China, 2013–2020 - Liu, Weiping; Qi, Jinlei; Liu, Jiangmei; Song, Yuqin; Wang, Lijun; Zhou, Maigeng; Ma, Jun; Zhu, Jun (Frontiers in Oncology, 2022)
Background: Lymphoma is a malignant disease that threatens human health and imposes a significant burden on the society burden; however, there are limited accurate mortality data on lymphoma in China. Methods: Mortality data of patients with lymphoma were extracted from the disease surveillance system of the Chinese Center for Disease Control and Prevention. Mortality was represented by the number of deaths, crude death rate, and age-standardized mortality rate. Temporal trends in mortality rates were examined using the fitting joinpoint models. Results: Lymphoma accounted for 31,225 deaths in 2020, of which 1,838 and 29,387 were due to Hodgkin lymphoma (HL) and non-Hodgkin lymphoma (NHL), respectively. The age-standardized mortality rate per 100,000 population was 1.76 for lymphoma, 0.10 for HL, and 1.66 for NHL. The mortality rate increased with age, reaching a peak in the age group of 80–84 years for HL and over 85 years for NHL. Moreover, the death risk due to lymphoma was approximately 1.5–2 times greater in males than in females in all age groups. The mortality rate was higher in eastern China than in central and western China, indicating a heterogeneous distribution at the provincial level. During 2013–2020, the mortality rate of lymphoma decreased by 1.85% (−22.94% for HL and −0.14% for NHL). Conclusion: The mortality rate of lymphoma varied by sex, age, and region (provinces). A significant decrease in the mortality rate of HL was demonstrated. This highlights the need to establish a differentiated strategy for disease control and prevention.